Terapi Sifilis Terkini - Rinandari, Ummi; Ellista Sari, Endra Yustin (PT. Kalbe Farma Tbk., 2020)
Sifilis adalah penyakit menular seksual yang disebabkan oleh infeksi bakteri Treponema pallidum. Penularan sifilis biasanya melalui kontak seksual dengan pasangan terinfeksi, kontak langsung dengan lesi terinfeksi, transfusi, dan jarum suntik. Sifilis dapat disembuhkan pada tahap awal infeksi, tetapi apabila tidak mendapat pengobatan adekuat dapat menjadi infeksi sistemik dan berlanjut ke fase laten. Pengobatan sifilis yang efisien sangat penting untuk mengontrol sifilis secara efektif.Syphilis is a sexually transmitted disease caused by a bacterial infection, Treponema pallidum. Transmission of syphilis is usually through sexual contact with an infected partner, direct contact with infected lesions, transfusions, and injection needles. Syphilis can be cured in the early stages of infection, but if it is not given adequate treatment it can become a systemic infection and progress to the latent phase. Efficient syphilis treatment is essential to control syphilis effectively.